Shen-Yuan-Dan Capsule Attenuates Atherosclerosis and Foam Cell Formation by Enhancing Autophagy and Inhibiting the PI3K/Akt/mTORC1 Signaling Pathway - Zhou, Mingxue; Ren, Pan; Zhang, Ying; Li, Sinai; Li, Mengjie; Li, Ping; Shang, Juju; Liu, Weihong; Liu, Hongxu (Frontiers in Pharmacology, 2019)
Background and Aim: The phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin complex 1 (mTORC1) signaling pathway plays a crucial role in autophagy and inflammation. Our previous studies demonstrated that Shen-Yuan-Dan Capsule (SYDC), a Chinese medicine used for treating angina pectoris, has anti-atherosclerotic and anti-inflammatory effects in mice. However, its effects on autophagy and the PI3K/Akt/mTORC1 signaling pathway remain unclear. This study aimed to explore the effects of SYDC on autophagy and PI3K/Akt/mTORC1 signaling in the apolipoprotein E knockout (ApoE−/−) mouse model and in macrophage-derived foam cells to delineate the underlying mechanism. Methods: After 6 weeks of high-fat diet, ApoE–/– mice were randomly grouped into control, Lipitor, low-SYDC (SYDC-L), middle-SYDC (SYDC-M), and high-SYDC (SYDC-H) groups (n = 10). The mice were intragastrically administered the respective treatment for 6 weeks. Murine RAW264.7 cells were stimulated with oxidized low-density lipoprotein (ox-LDL) (80 µg/ml) for 24 h and then pretreated with SYDC freeze-dried powder for another 24 h. Cells treated with SYDC were co-cultured for 24 h with LY294002, tricirbine, and rapamycin to investigate the effects on the PI3K/Akt/mTORC1 signaling pathway. Results: SYDC ameliorated blood lipid levels, reduced the atherosclerotic index and plaque areas in the aortic root in mice, and inhibited total cholesterol (TC) levels and cholinesterase (ChE)/TC ratios in ox-LDL stimulated macrophages. Moreover, SYDC up-regulated Beclin1 and LC3II/I proteins in mice and in the ox-LDL–stimulated macrophages. Moreover, SYDC inhibited AKT phosphorylation at Ser473 and mTOR phosphorylation at Ser2448 in mice and in ox-LDL–stimulated macrophages. Furthermore, SYDC’s inhibitory of ChE/TC ratios in ox-LDL–stimulated macrophages was not changed by selective inhibition of the PI3K/Akt/mTORC1 pathway. Conclusions: Our results highlight that SYDC treatment attenuates foam cell formation by promoting autophagy via inhibiting activation of the PI3K/Akt/mTORC1 signaling pathway. This study provides new insights into the molecular mechanism underlying SYDC’s therapeutic potential for treating atherosclerosis.